(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The first finding in Lombardy (Northern Italy) of the Nearctic hopper Acanalonia conica (Say) (Fulgoromorpha Acanaloniidae) is reported. This is the second Italian record, after the first one of 2004 from Venetia. The introduction of A. conica in Italy was foreseen and feared; now this species is really a further potential phytophagous pest accidentally introduced into Italy in these last few years. The possible damage caused by this polyphagous insect is summarized briefly.